Lung cancer and socioeconomic status in a pooled analysis of case-control studies - Hovanec, Jan; Siemiatycki, Jack; Conway, David I; Olsson, Ann; Stücker, Isabelle; Guida, Florence; Jöckel, Karl-Heinz; Pohlabeln, Hermann; Ahrens, Wolfgang; Brüske, Irene; Wichmann, Heinz-Erich; Gustavsson, Per; et al. (PLoS One, 2018)
BACKGROUND: An association between low socioeconomic status (SES) and lung cancer has been observed in several studies, but often without adequate control for smoking behavior. We studied the association between lung cancer and occupationally derived SES, using data from the international pooled SYNERGY study. METHODS: Twelve case-control studies from Europe and Canada were included in the analysis. Based on occupational histories of study participants we measured SES using the International Socio-Economic Index of Occupational Status (ISEI) and the European Socio-economic Classification (ESeC). We divided the ISEI range into categories, using various criteria. Stratifying by gender, we calculated odds ratios (OR) and 95% confidence intervals (CI) by unconditional logistic regression, adjusting for age, study, and smoking behavior. We conducted analyses by histological subtypes of lung cancer and subgroup analyses by study region, birth cohort, education and occupational exposure to known lung carcinogens. RESULTS: The analysis dataset included 17,021 cases and 20,885 controls. There was a strong elevated OR between lung cancer and low SES, which was attenuated substantially after adjustment for smoking, however a social gradient persisted. SES differences in lung cancer risk were higher among men (lowest vs. highest SES category: ISEI OR 1.84 (95% CI 1.61-2.09); ESeC OR 1.53 (95% CI 1.44-1.63)), than among women (lowest vs. highest SES category: ISEI OR 1.54 (95% CI 1.20-1.98); ESeC OR 1.34 (95% CI 1.19-1.52)). CONCLUSION: SES remained a risk factor for lung cancer after adjustment for smoking behavior.
Keywords: pracovní expozice; odds ratio; Humans; lidé středního věku; Occupational Exposure; Lung Neoplasms; logistické modely; Europe; kouření; Middle Aged; Logistic Models; Smoking; Risk Factors; Canada; mužské pohlaví; Age Factors; nádory plic; Sex Factors; Evropa; rizikové faktory; ženské pohlaví; sexuální faktory; věkové faktory; Kanada; lidé; Odds Ratio; společenská třída; Aged; Social Class; senioři; Male; Female